EXPLORING MULTIDIMENSIONAL CONSTRUCTS OF TRUST IN PROCUREMENT PRACTICES: AN EVIDENCE FROM MALAYSIA - Aseh, Khairi; Kenny, Kamal; Pathmanathan, Ravindran (Archives of Business Research, 2020)
During the last two decades, the study of procurement practices impacts on business performance has generated interest among many researchers. Yet very little literature deals specifically with how company success is affected by the procurement activities of companies. In fact, most of the papers reviewed on procurement activities are qualitative rather than empirical in nature. As a result, several businesses are starting to pursue further aspects of business-performing procurement activities. Against this backdrop, this work aims to fill this vacuum by performing empirical case studies at 28 companies operating in the worst ever chaotic climate in the world. The results of this research study attempt to determine the interconnection between the procurement practices of companies and business performance related to the seven trust attributes (commitment; openness; integrity, proximity, competence; reliability and security).